Mitochondrial-derived gene expression in hibernation: tissue-specific responses in the thirteen-lined ground squirrel - Sarah Viola Emser; Eva Millesi (Open Biology)
Hibernation is a remarkable physiological adaptation in many mammals, characterized by prolonged torpor and profound metabolic suppression. Despite its importance, the molecular mechanisms regulating mitochondrial-derived gene expression during hibernation remain poorly understood. In this study, we analysed mitochondrial gene expression across multiple tissues of the hibernating thirteen-lined ground squirrel (Ictidomys tridecemlineatus) using publicly available RNA sequencing (RNA-seq) data. We assessed all known mitochondrial DNA-derived transcripts—including mitochondrial mRNAs, mitochondrial-derived peptides and proteins (MDPs), rRNAs, and long non-coding RNAs (lncRNAs)—in the liver, adrenal gland, three brain regions, and brown adipose tissue (BAT) across different hibernation states. Our findings reveal distinct tissue-specific expression patterns of mitochondrial transcripts. Differential expression was observed in three of the six tissues analysed (liver, adrenal gland, and BAT) while no significant changes were detected in the three brain regions. In tissues exhibiting differential expression, a consistent pattern emerged: lncRNAs such as Mdl1, Mdl1as, and lncCyb were generally upregulated, whereas mRNAs, including a novel transcript encoding the putative mitochondrial protein Rudel, were predominantly downregulated. These results provide new insights into mitochondrial gene regulation during hibernation and highlight tissue-specific adaptations at the level of mitochondrial gene expression.